Role of Chloride on Corrosion of Carbon Steel Reinforcing Bar in Simulate Concrete Electrolyte - Abdulkareem M.A. Al-Sammarraie (Journal of Global Pharma Technology, 2016)
It is well known that chloride ion plays an important role in the destruction of various kinds of concrete structures such as bridges of buildings and reservoirs because of the corrosion of carbon steel reinforcement bar, causing huge human and material damages. In this study, the effect of saline conditions on carbon steel reinforcement was investigated artificial concrete solution in a range of sodium chloride concentrations from 0.5 to 4.5% and at temperatures of 20°C to 50°C. Three electrodes potentiostat was used to measure the corrosion rate and the probability of pitting corrosion through Tafel and cyclic polarization plots respectively. The measurements were supported using other techniques; atomic force microscopy and optical light microscopy. The results showed an increase in corrosion rates of the carbon steel reinforcing bar at all chloride ion concentrations, and increased with increasing the concentration and the temperature, all chloride concentrations showed susceptibility to pitting corrosion and highly depend on NaCl continents.Keyword: Reinforcing bar, Pitting, Artificial concrete solution.